2023
DOI: 10.1002/advs.202301802
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Epigenetic Reprogramming of Mesenchymal to Epithelial States Using the CRISPR/dCas9 Platform in Triple Negative Breast Cancer

Abstract: Epithelial-mesenchymal transition (EMT) is a reversible transcriptional program invoked by cancer cells to drive cancer progression.Transcription factor ZEB1 is a master regulator of EMT, driving disease recurrence in poor-outcome triple negative breast cancers (TNBCs). Here, this work silences ZEB1 in TNBC models by CRISPR/dCas9-mediated epigenetic editing, resulting in highly-specific and nearly complete suppression of ZEB1 in vivo, accompanied by long-lasting tumor inhibition. Integrated "omic" changes prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…ROR1 is a type I transmembrane protein, that expresses during cancer and embryonic development and, has been identified as an oncofetal protein (Nicholas Borcherding, Pote and Gacche (2023) Frontiers in Molecular Biosciences frontiersin.org 2014). The aggressive behavior of various human cancers has been linked to the upregulation of ROR1.…”
Section: Crispr/cas9 and Receptor Tyrosine Kinase-like Orphan Recepto...mentioning
confidence: 99%
See 1 more Smart Citation
“…ROR1 is a type I transmembrane protein, that expresses during cancer and embryonic development and, has been identified as an oncofetal protein (Nicholas Borcherding, Pote and Gacche (2023) Frontiers in Molecular Biosciences frontiersin.org 2014). The aggressive behavior of various human cancers has been linked to the upregulation of ROR1.…”
Section: Crispr/cas9 and Receptor Tyrosine Kinase-like Orphan Recepto...mentioning
confidence: 99%
“…In a recent study, Waryah et alemployed a TNBC model and achieved complete silencing of ZEB1 utilizing dCas9. Consequently, they observed a remarkably high specificity and near-total suppression of ZEB1 under in vivo condition ( Waryah et al, 2023 ).…”
Section: Dcas9mentioning
confidence: 99%
“…CUT&RUN and base editing indicated that the NF-Y activator occupied the proximal CCAAT box, and the BCL11A initiated inhibition by binding competitively with NF-Y. Besides inhibiting gene expression, the dCas9-KRAB fusion protein can induce DNA methylation to explore the epigenome [46,47]. Thakore et al [29] targeted dCas9-KRAB to the HS2 enhancer that realizes specific induction of H3K9 trimethylation, which silenced the expression of multiple globin genes.…”
Section: Crispri Tools: Suppressing Gene Expression At the Transcript...mentioning
confidence: 99%
“…The ZEBs are best known as key drivers of EMT by repressing CDH1 and the proepithelial miR-200 family members. Downstream targets of ZEB1 and ZEB2 have been well studied in the context of breast cancer and include key genes involved in epithelial plasticity and cellular polarity genes [88][89][90]. By targeting promoters of pro-epithelial genes, ZEBs are dominant regulators of EMT and tumor progression.…”
Section: Zeb1 and Zeb2mentioning
confidence: 99%